Avaliação da produção de H2 a partir da reforma a seco do metano e eletrólise da água - Pinto, Pedro Henrique Cavalcante (Universidade Federal de São Carlos, 2022)
The global energy demand since the industrial revolution has grown continuously and is projected to grow by 50% in the next 30 years. Following the current proportion of energy sources, it becomes environmentally unsustainable to supply this amount with a proportion of 83.7% coming from non-renewable sources. Several alternative and more sustainable sources have emerged and are still under development to reverse this proportion. One of them is the use of hydrogen gas, H2, in energy supply and as a fuel, replacing fossil fuels. There are different ways of producing H2, the most conventional ones with a carbon footprint of medium to high intensity, thus generating gray or blue hydrogen. There are alternatives such as water electrolysis that can guarantee the production of gas without the emission of any gaseous pollutants (CO, CH4, CO2, among others). In this work, the Aspen Plus® process simulator was used to analyze the production of hydrogen by two routes: the dry reforming of methane and the electrolysis of water. For the first route, the Gibbs reactor was used to evaluate the thermodynamic limits of the reaction and the production capacity. Sequentially, the kinetics presented by Luyben (2014) were used to simulate the production of H2 using a PBR reactor considering a production capacity sufficient to meet approximately 6.0% of the energy demand of the northern region of Brazil. The production of H2 with the reactor at a pressure of 1.0 bar, feed ratio CH4/CO2 = 1/1.1 and temperatures of 800 and 920 °C were 1,587 and 1,649 kg H2 s-1, respectively. For the second route, data from Sànchez et al. (2019) for the calculations of the electrolytic cell needed to perform the electrolysis of water and the stoichiometric reactor (RSTOIC) and separation units were used for the development of the process on the simulator. The production of H2 was low, with conversion of approximately 0.18% of the water fed with a flow of approximately 50 kmols h-1 and operating conditions of 75°C and 7 bar. To increase the production of H2, it is necessary to improve and optimize the activity of electrolytic cells and use clean energy from wind, solar or hydraulic sources.
Evaluation of H2 production from dry reforming of methane and water electrolysis
Keywords: Hidrogênio; Hydrogen; Eletrólise da água; Water electrolysis; Reforma a seco do metano; Dry reforming of methane; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA